Explore a world of knowledge and get your questions answered on IDNLearn.com. Ask anything and receive immediate, well-informed answers from our dedicated community of experts.
Sagot :
To determine for what values of [tex]\( k \)[/tex] the function [tex]\( f \)[/tex] defined by
[tex]\[ f(x) = \begin{cases} \frac{|x-3|}{x-3}, & \text{if } x > 3 \\ k, & \text{if } x \leq 3 \end{cases} \][/tex]
is continuous at [tex]\( x = 3 \)[/tex], we need to ensure the limit from the left and the limit from the right at [tex]\( x = 3 \)[/tex] are equal, and also equal to the function value at [tex]\( x = 3 \)[/tex].
First, let's simplify [tex]\( \frac{|x-3|}{x-3} \)[/tex] for [tex]\( x > 3 \)[/tex]:
For [tex]\( x > 3 \)[/tex]:
[tex]\[ |x-3| = x-3 \implies \frac{|x-3|}{x-3} = \frac{x-3}{x-3} = 1. \][/tex]
Thus, for [tex]\( x > 3 \)[/tex], [tex]\( f(x) = 1 \)[/tex].
Now, the function can be rewritten as:
[tex]\[ f(x) = \begin{cases} 1, & \text{if } x > 3 \\ k, & \text{if } x \leq 3 \end{cases} \][/tex]
To check continuity at [tex]\( x = 3 \)[/tex], we need the following to hold:
1. [tex]\(\lim_{x \to 3^-} f(x)\)[/tex] exists.
2. [tex]\(\lim_{x \to 3^+} f(x)\)[/tex] exists.
3. [tex]\(f(3)\)[/tex] is defined.
4. [tex]\(\lim_{x \to 3^-} f(x) = \lim_{x \to 3^+} f(x) = f(3)\)[/tex].
Let's calculate each condition:
1. [tex]\[ \lim_{x \to 3^-} f(x) \rightarrow \lim_{x \to 3^-} k = k. \][/tex]
2. [tex]\[ \lim_{x \to 3^+} f(x) \rightarrow \lim_{x \to 3^+} 1 = 1. \][/tex]
3. [tex]\[ f(3) = k. \][/tex]
For [tex]\( f(x) \)[/tex] to be continuous at [tex]\( x = 3 \)[/tex]:
[tex]\[ \lim_{x \to 3^-} f(x) = \lim_{x \to 3^+} f(x) = f(3). \][/tex]
Therefore,
[tex]\[ k = 1. \][/tex]
As a result, the function [tex]\( f \)[/tex] is continuous at [tex]\( x = 3 \)[/tex] if and only if [tex]\( k = 1 \)[/tex].
Hence, the value of [tex]\( k \)[/tex] is 1, which is unfortunately not listed among the options.
For the given answer for the limit problem
[tex]\[ \lim_{x \rightarrow 0} \frac{\sin(7x) - \sin(4x)}{3x} = 1. \][/tex]
Let's analyze the problem:
Using L'Hopital's Rule for the limit,
[tex]\[ =\lim_{x \rightarrow 0} \frac{7\cos(7x) - 4\cos(4x)}{3}. \][/tex]
When [tex]\( x \to 0\)[/tex],
[tex]\[ =\frac{7\cos(0) - 4\cos(0)}{3} = \frac{7 - 4}{3} = 1. \][/tex]
Thus, the correct answer is [tex]\( \boxed{1} \)[/tex].
[tex]\[ f(x) = \begin{cases} \frac{|x-3|}{x-3}, & \text{if } x > 3 \\ k, & \text{if } x \leq 3 \end{cases} \][/tex]
is continuous at [tex]\( x = 3 \)[/tex], we need to ensure the limit from the left and the limit from the right at [tex]\( x = 3 \)[/tex] are equal, and also equal to the function value at [tex]\( x = 3 \)[/tex].
First, let's simplify [tex]\( \frac{|x-3|}{x-3} \)[/tex] for [tex]\( x > 3 \)[/tex]:
For [tex]\( x > 3 \)[/tex]:
[tex]\[ |x-3| = x-3 \implies \frac{|x-3|}{x-3} = \frac{x-3}{x-3} = 1. \][/tex]
Thus, for [tex]\( x > 3 \)[/tex], [tex]\( f(x) = 1 \)[/tex].
Now, the function can be rewritten as:
[tex]\[ f(x) = \begin{cases} 1, & \text{if } x > 3 \\ k, & \text{if } x \leq 3 \end{cases} \][/tex]
To check continuity at [tex]\( x = 3 \)[/tex], we need the following to hold:
1. [tex]\(\lim_{x \to 3^-} f(x)\)[/tex] exists.
2. [tex]\(\lim_{x \to 3^+} f(x)\)[/tex] exists.
3. [tex]\(f(3)\)[/tex] is defined.
4. [tex]\(\lim_{x \to 3^-} f(x) = \lim_{x \to 3^+} f(x) = f(3)\)[/tex].
Let's calculate each condition:
1. [tex]\[ \lim_{x \to 3^-} f(x) \rightarrow \lim_{x \to 3^-} k = k. \][/tex]
2. [tex]\[ \lim_{x \to 3^+} f(x) \rightarrow \lim_{x \to 3^+} 1 = 1. \][/tex]
3. [tex]\[ f(3) = k. \][/tex]
For [tex]\( f(x) \)[/tex] to be continuous at [tex]\( x = 3 \)[/tex]:
[tex]\[ \lim_{x \to 3^-} f(x) = \lim_{x \to 3^+} f(x) = f(3). \][/tex]
Therefore,
[tex]\[ k = 1. \][/tex]
As a result, the function [tex]\( f \)[/tex] is continuous at [tex]\( x = 3 \)[/tex] if and only if [tex]\( k = 1 \)[/tex].
Hence, the value of [tex]\( k \)[/tex] is 1, which is unfortunately not listed among the options.
For the given answer for the limit problem
[tex]\[ \lim_{x \rightarrow 0} \frac{\sin(7x) - \sin(4x)}{3x} = 1. \][/tex]
Let's analyze the problem:
Using L'Hopital's Rule for the limit,
[tex]\[ =\lim_{x \rightarrow 0} \frac{7\cos(7x) - 4\cos(4x)}{3}. \][/tex]
When [tex]\( x \to 0\)[/tex],
[tex]\[ =\frac{7\cos(0) - 4\cos(0)}{3} = \frac{7 - 4}{3} = 1. \][/tex]
Thus, the correct answer is [tex]\( \boxed{1} \)[/tex].
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. IDNLearn.com is committed to providing the best answers. Thank you for visiting, and see you next time for more solutions.